Infrastructure Development in Papua: Features and Challenges - Fadhli Zul Fauzi; A. A. Gede Brahmantya Murti; Laili Alfiati Imamah; Nimas Hapsari (Policy & Governance Review, 2019)
This article aims to examine the issue of infrastructure development in Papua Province, Indonesia. This article specifically discusses the problems confronted during the process of infrastructure development in Jayapura and the challenges in expanding them. The method used in this study is the qualitative method with a case study approach, wherein the infrastructure development case selected is the Papua Bangkit Stadium and Holtekamp Bridge located in Jayapura. Both infrastructure development cases serve as sample cases that show the extent of infrastructure development impact in Papua, and the issues that were confronted, starting from the development process up to the expansion. The study results indicate that although previous studies have shown positive correlation between development and welfare, in reality, there are several problems occurring in Papua’s infrastructure development. Preparedness of human resources, cultural issues, and weak coordination between every level of regional government institution, these are the main problems in Papua’s infrastructure development. This article is expected to assist in resolving the issues found in Papua’s infrastructure development, and to provide recommendations for resolving those issues.